Kemampuan Berpikir Kritis Peserta Didik Pada Pembelajaran Fisika Materi Getaran Harmonik Dengan Pendekatan Saintifik - Risma Hidayati; Muh. Makhrus; Sutrio Sutrio (Kappa Journal, 2022)
. This study aims to determine the critical thinking skills of students on the material of harmonic vibrations at SMAN 1 Praya Tengah through a scientific approach. This research is a development research with 4D model. The population in this study were all students of class X MIPA 1 SMAN 1 Praya Tengah, totaling 24 students. Data collection on critical thinking skills was carried out by conducting a pretest and posttest in the form of a description test of 10 questions. The results of data analysis determine the level of students' critical thinking skills using a scientific approach. The results showed that the scientific approach can improve critical thinking skills with an n-gain score of 0.578 in the medium category. The scientific approach has been successfully applied to improve critical thinking skills.